Effects of Berberine on the Gastrointestinal Microbiota - Zhang, Lichao; Wu, Xiaoying; Yang, Ruibing; Chen, Fang; Liao, Yao; Zhu, Zifeng; Wu, Zhongdao; Sun, Xi; Wang, Lifu (Frontiers in Cellular and Infection Microbiology, 2021)
The gastrointestinal microbiota is a multi-faceted system that is unraveling novel contributors to the development and progression of several diseases. Berberine has been used to treat obesity, diabetes mellitus, atherosclerosis, and metabolic diseases in China. There are also clinical trials regarding berberine use in cardiovascular, gastrointestinal, and endocrine diseases. Berberine elicits clinical benefits at standard doses and has low toxicity. The mechanism underlying the role of berberine in lipid‐lowering and insulin resistance is incompletely understood, but one of the possible mechanisms is related to its effect on the gastrointestinal microbiota. An extensive search in electronic databases (PubMed, Scopus, Embase, Web of Sciences, Science Direct) was used to identify the role of the gastrointestinal microbiota in the berberine treatment. The aim of this review was to summarize the pharmacologic effects of berberine on animals and humans by regulation of the gastrointestinal microbiota.